2020
DOI: 10.1002/open.202000042
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design and Synthesis of Piperidinol‐Containing Molecules as New Mycobacterium abscessus Inhibitors

Abstract: Non‐tuberculous mycobacterium (NTM) infections, such as those caused by Mycobacterium abscessus, are increasing globally. Due to their intrinsic drug resistance, M. abscessus pulmonary infections are often difficult to cure using standard chemotherapy. We previously demonstrated that a piperidinol derivative, named PIPD1, is an efficient molecule both against M. abscessus and Mycobacterium tuberculosis, the agent of tuberculosis, by targeting the mycolic acid transporter MmpL3. These results prompted us to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Most frequently, LBDD uses the structure–activity or structure–property relationship (SAR/SPR) studies, wherein the chemical structure of the ligand is correlated to its activity (or property) from a model developed from previously acquired data. The SAR approach was successfully used to evaluate a series of piperidinol derivatives [ 123 ], based on a previous finding that piperidinol efficiently works against M. abscessus and M. tuberculosis by targeting the mycolic acid transporter MmpL3 [ 124 ]. A series of similar compounds were synthesized and tested in vitro, and the data were used to create a SAR model to guide the design of subsequent derivatives, as well as to identify the molecular sites that can be effectively modulated.…”
Section: Models For Drug Discovery Against Ntmmentioning
confidence: 99%
“…Most frequently, LBDD uses the structure–activity or structure–property relationship (SAR/SPR) studies, wherein the chemical structure of the ligand is correlated to its activity (or property) from a model developed from previously acquired data. The SAR approach was successfully used to evaluate a series of piperidinol derivatives [ 123 ], based on a previous finding that piperidinol efficiently works against M. abscessus and M. tuberculosis by targeting the mycolic acid transporter MmpL3 [ 124 ]. A series of similar compounds were synthesized and tested in vitro, and the data were used to create a SAR model to guide the design of subsequent derivatives, as well as to identify the molecular sites that can be effectively modulated.…”
Section: Models For Drug Discovery Against Ntmmentioning
confidence: 99%
“…Molecular modeling of the piperidinol derivative reveals that the nitrogen of 13 interacts with the carboxylic group of D618 and the hydroxyl of 13 interacts with the hydroxyl of Y219 through hydrogen bonding. Ring B is required to interact with the phenyl ring of F262 and F622 through π-π stacking interactions [ 75 ].…”
Section: Mycolic Acid Biosynthesismentioning
confidence: 99%
“…More pharmacokinetic parameters were assessed, such as clearance rate, volume of distribution, and elimination half-life, none of which differ significantly from the values obtained by Low et al The clearance rate and peripheral volume of distribution are 6.9 mL/min and 2.0 L, and the elimination half-life is about 3.2 h. Compound 13 has poor oral bioavailability, calculated at less than 1% [ 59 ]. Currently, there are ongoing research efforts to improve the metabolic stability and polarity of this class of compound [ 75 ].…”
Section: Mycolic Acid Biosynthesismentioning
confidence: 99%
“…The species is resistant to most antibiotics and disinfectants, and many treatments require the use of an association of multiple drugs. In a recent study, de Ruyck et al [2] focused their attention on the design, synthesis, and evaluation of piperidinol-containing molecules (Figure 1) that target the flippase activity of the mycolic acid transporter MmpL3. They have demonstrated that such an inhibition can result directly in the death of the pathogen.…”
Section: Highlighted By Jean Jacques Vanden Eyndementioning
confidence: 99%